In vivo wound healing potential of hylocereus costaricensis (Red Dragon Fruit) methanolic crude peel extract ointment in male sprague dawley rats - Larraquel, Ylena D., Magsino, Thea Victoria B., Pascual, Alecxandra Dominique C., Rodriguez, Kyle Trishka P., Simbol, Audrrie Claire M. 4 0 16; 5
ABSTRACT: This study evaluated the in vivo wound healing potential of Hylocereus costaricensis red dragon fruit (RDF) methanolic crude peel extract ointment in terms of wound healing rate, complete epithelialization duration, and histological parameters. Adult male Sprague Dawley rats (N=35) at 6 weeks, weighing 100-200 grams were randomly assigned as Group I Negative Control (simple ointment base), Group Il Positive Control (15% avocado peel extract), and three RDF peel methanolic crude peel extract ointment concentrations: Group Ill Treatment 1 (4.6%), Group IV Treatment 2 (6.9%), and Group V Treatment 3 (9.2%) (w/w). Two dermal punch wounds were induced in rats using 6 mm biopsy punch via through-and-through wounding. Treatments were applied once daily wherein wounds at Days 0, 1, 3, 7, 14, and 21 were documented morphometrically and manually. One rat from each group was biopsied for the histopathological analysis on Days 3 and 14. Results showed that the treatment groups did not exhibit wound healing potential since favorable results for wound healing rate and epithelialization duration were observed in negative control. The histopathological findings suggested potential early stage wound healing; however, statistical analyses showed insignificance. These findings could be due to insufficiency of phytochemicals in the treatment, compromission of treatment delivery during scabbing period, and homogeneity of treatment formulation. The researchers primarily recommend utilization of apposite solvent for extraction and standard for quantification of major phytochemicals, incorporation of RDF extract into high-moisture topical treatment form and include control groups that involve sterile lifting of scabs during treatment application. Keywords: Hylocereus costaricensis, red dragon fruit peel, Sprague Dawley rats, wound healing, wound healing rate, epithelialization, histopathological analysis, inflammation, collagen deposition
Undergraduate Thesis: (BS in Biology major in Medical Biology) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2